Deep Brain Stimulation of the Subthalamic Nucleus Alters the Cortical Profile of Response Inhibition in the Beta Frequency Band: A Scalp EEG Study in Parkinson's Disease - Swann, Nicole; Poizner, Howard; Houser, Melissa; Gould, Sherrie; Greenhouse, Ian; Cai, Weidong; Strunk, Jon; George, Jobi; Aron, Adam R. (The Journal of neuroscience, 2011)
Stopping an initiated response could be implemented by a fronto-basal-ganglia circuit, including the right inferior frontal cortex (rIFC) and the subthalamic nucleus (STN). Intracranial recording studies in humans reveal an increase in beta-band power (∼16–20 Hz) within the rIFC and STN when a response is stopped. This suggests that the beta-band could be important for communication in this network. If this is the case, then altering one region should affect the electrophysiological response at the other. We addressed this hypothesis by recording scalp EEG during a stop task while modulating STN activity with deep brain stimulation. We studied 15 human patients with Parkinson's disease and 15 matched healthy control subjects. Behaviorally, patients OFF stimulation were slower than controls to stop their response. Moreover, stopping speed was improved for ON compared to OFF stimulation. For scalp EEG, there was greater beta power, around the time of stopping, for patients ON compared to OFF stimulation. This effect was stronger over the right compared to left frontal cortex, consistent with the putative right lateralization of the stopping network. Thus, deep brain stimulation of the STN improved behavioral stopping performance and increased the beta-band response over the right frontal cortex. These results complement other evidence for a structurally connected functional circuit between right frontal cortex and the basal ganglia. The results also suggest that deep brain stimulation of the STN may improve task performance by increasing the fidelity of information transfer within a fronto-basal-ganglia circuit.